Report of the Working Group on the Assessment of Pandalus Stocks ... - ICES (ICES Expert Group reports (until 2018), 2023)
The Working Group on the Asse5sment of Pandalus Stocks (Chairman: Mr S. Munch-Petersen) met at lCES Headquarters from 13-17 February 1989 (C.Res.1988/2:4:1) to assess the status of the stocks of Pandalus borealis in the North Sea, Skagerrak, and Kattegat. ...